BAHASA, PIKIRAN, DAN REALITAS MERUPAKAN KESATUAN SISTEM YANG TIDAK DAPAT DIPISAHKAN - Setyonegoro, Agus (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This article aim to explain "language, mind, and reality is unity of inseparable system". For the purpose, there is two the fundamental elaborated at this article, that is (1) reality and function of language and (2) the relation of mind, language, and reality. Description firstly include (a) linguistic reality and (b) function of language. Including second description (a) the relation of mind, language, and reality and (b) clarity thinks and having language.Key Words: language, mind, reality